IV. Maps - Ordnance Survey (Ireland) (1882)
Collection of maps held by Kirwan’s of Tuam, for a variety of areas in Galway.
Keywords: Kirwan family; Maps and Surveys -- Ireland -- Galway (County); Administration of estates -- Ireland -- Galway (County); Dalgin (Galway, Ireland); Tuam (Galway, Ireland)